2008
DOI: 10.2137/145960608786118785
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of soil phosphorus tests in predicting the potential risk of phosphorus loss from pasture soil

Abstract: The objective of this study was to examine the effects of urine and dung additions on the phosphorus (P) chemistry of pasture land and to compare the sensitivity of two soil extraction methods in assessing the P-loading risk. In a field experiment, urine and dung were added to soil in amounts corresponding to single excrement portions and the soil samples, taken at certain intervals, were analysed for pH H2O , acid ammonium acetate extractable P (P Ac ) and water extractable total P (TP w ), and molybdate rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although P concentrations in dung can be similar, the amount of dung excreted by cattle per day is far greater than by sheep (∼25 kg/day per head for cattle and 1.4 kg/day per head for sheep) (Haynes & Williams, 1993). It is also possible that N deposition in urine may have altered soil P concentrations because sheep tend to urinate more than cattle (Soinne et al. , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Although P concentrations in dung can be similar, the amount of dung excreted by cattle per day is far greater than by sheep (∼25 kg/day per head for cattle and 1.4 kg/day per head for sheep) (Haynes & Williams, 1993). It is also possible that N deposition in urine may have altered soil P concentrations because sheep tend to urinate more than cattle (Soinne et al. , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the importance of the relationship of soil N and boreal vegetation cover. So far, soil P in boreal forests has received relatively little interest compared to N, and most studies regarding P have concentrated on former agricultural lands (Peltovuori 2007;Soinne et al 2008) or on peatlands (e.g. Moilanen et al 2010).…”
Section: Discussionmentioning
confidence: 99%